2007
DOI: 10.1053/j.gastro.2007.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Wilson’s Disease Mutations in ATP7B Are Associated With Enhanced Binding to COMMD1 and Reduced Stability of ATP7B

Abstract: Background/Aims-Wilson disease is characterized by hepatic copper overload and caused by mutations in the gene encoding the copper transporting P-type ATPase ATP7B. ATP7B interacts with COMMD1, a protein that is deleted in Bedlington terriers with hereditary copper toxicosis. Here we characterized the implications of the interaction between COMMD1 and ATP7B in relation to the pathogenesis of Wilson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
162
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(177 citation statements)
references
References 36 publications
10
162
1
2
Order By: Relevance
“…Constructs and Reagents-ATP7B cDNA constructs encoding WT ATP7B, ATP7B(MBD 1-6del), and ATP7B(MBD 3-5del), and N-terminal FLAG-tagged WT-ATP7B-FLAG and ATP7B-G85V-FLAG were generated previously (23,24). Clusterin cDNA in pIREShyg1 (Clontech) was kindly provided by Saverio Bettuzzi (University of Parma).…”
Section: Methodsmentioning
confidence: 99%
“…Constructs and Reagents-ATP7B cDNA constructs encoding WT ATP7B, ATP7B(MBD 1-6del), and ATP7B(MBD 3-5del), and N-terminal FLAG-tagged WT-ATP7B-FLAG and ATP7B-G85V-FLAG were generated previously (23,24). Clusterin cDNA in pIREShyg1 (Clontech) was kindly provided by Saverio Bettuzzi (University of Parma).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the protein COMMD1 (Copper Metabolism Murr1 Domain) was recently shown to interact with the metal-binding domains of ATP7B and this appeared to regulate overall ATP7B stability via the ER degradation pathway (de Bie et al 2007;Materia et al 2012). The binding sites on neither protein nor the physical mechanism resulting in ER degradation (interaction causing protein destabilization or triggering of a cellular signal) are known.…”
Section: Interactions With Other Proteins and New Functionsmentioning
confidence: 99%
“…Although it has been reported that COMMD1 binds Cu 2? [112], a direct and copper-independent interaction between the amino terminus of ATP7B and COMMD1 has been characterized [113,114]. Transient knockdown of COMMD1 by RNA interference results in increased cellular copper levels in HEK293T cells [115][116][117].…”
Section: Regulation Of Copper Transport By Protein-protein Interactionsmentioning
confidence: 99%
“…Together, these data suggest that ATP7B and COMMD1 cooperate in cellular copper export, which might be the underlying defect in Bedlington terriers affected by copper toxicosis. Interestingly, the interaction between COMMD1 and ATP7B is markedly increased when Wilson-disease-associated mutations of ATP7B are present [114,118]. These mutations are associated with misfolding, mislocalization of ATP7B to the endoplasmic reticulum, and decreased protein expression due to increased proteasomal degradation.…”
Section: Regulation Of Copper Transport By Protein-protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation